Understanding Music Past and Present - Clark, Alan; Heflin, Thomas; Kluball, Jeffery; Kramer, Elizabeth (Open textbook library., 2015)
Understanding Music: Past and Present is an open Music Appreciation textbook co-authored by music faculty across Georgia. The text covers the fundamentals of music and the physics of sound, an exploration of music from the Middle Ages to the present day, and a final chapter on popular music in the United States.